Reforming an insider-outsider labor market: The Spanish experience - Samuel Bentolila; Juan Jose Dolado; Juan F. Jimeno (Center for Economic Studies and ifo Institute (CESifo), 2011)
This paper presents a case study on reforming a very dysfunctional labor market with a deep insider-outsider divide, namely the Spanish case. We show how a dual market, with permanent and temporary employees makes real reform much harder, and leads to purely marginal changes that do not alter the fundamental features of labor market institutions. While the Great Recession and the start of the sovereign debt crisis triggered two labor reforms, the political economy equilibrium has not allowed them to be transformational enough.
Keywords: H29; J23; J38; J41; J64; 330; temporary contracts; dualism; labor market reform; political economy; Great Recession; Arbeitsmarktflexibilität; Insider-Outsider-Modell; Reform; Befristeter Arbeitsvertrag; Dualer Arbeitsmarkt; Spanien